Pathways to greater government accountability for breaches of their obligations in relation to doping in sport: A legal analysis - Pavot, David (Frontiers in Sports and Active Living, 2023)
The state-sponsored doping system in Russia has highlighted the shortcomings of the anti-doping system with regard to state responsibility. This issue is currently being addressed as a panel at the WADA 2022 symposium looked at the issue and UNESCO has just established a working group on the issue. The purpose of this article is to examine the relevance of the principles of international state responsibility as applied to doping, while identifying ways in which a framework of accountability can be developed.